Surgical Pearls for Pterygium Surgery (Canadian Eye Care Today, 2025)
Pterygium, a common ocular surface disorder, manifests as a wing-shaped degenerative fibrovascular benign growth characterized by the fibrovascular proliferation of conjunctival tissue onto the cornea (Figure 1). This condition often results from prolonged exposure to ultraviolet light, dry eye conditions, or chronic irritation. On histopathology, there is classically elastotic degeneration of the conjunctival stroma with overgrowth of blood vessels and fibrous tissue, i.e., a fibro-proliferative reaction. While small and asymptomatic lesions may be managed conservatively, surgical excision becomes necessary when the lesion threatens vision, causes significant discomfort, or results in cosmetic concerns. A pterygium with documented growth that extends toward the visual axis should be removed before it reaches the central cornea. However, due to its high recurrence rate and variability in presentation, surgical management of pterygium requires attention to detail and a thorough understanding of optimal techniques.